Perlindungan Hukum Terhadap Korban Perdagangan Orang yang Dijadikan Pekerja Seks Komersial di Wilayah Hukum Polda DIY - Agus Setiyawan; M. Hatta (Kajian Hasil Penelitian Hukum, 2019)
This study aims to analyze the steps of the police in the process of law enforcement in the commercial criminal acts of people who disguised commercial sex workers in the area of DIY Local Police, but also aimed to analyze the legal protection carried out by DIY Regional Police to victims of trafficking of persons employed as commercial sex workers, so law enforcement by providing legal protection facilities for such crimes can have a positive impact on the victims.The approach used by the author is the empirical juridical approach. Law enforcement in the criminalization of the Crimes of Trafficking in Persons committed by the Regional Police of DIY is done by 3  ways that is preemptive, preventive and repressive. Implementation of law enforcement in preemptive way is done by doing some activity agenda such as conducting socialization related to effect and impact of people trafficking, coordinating to all ranks in Local Police of DIY to be conducted socialization of danger of crime of trafficking of person , while repressive law enforcement is done when there are reports from the community there has been a crime of trafficking in persons somewhere. Related to the legal protection against the victims conducted by the Regional Police of DIY was conducted in the form of giving advocacy to the victim in cooperation with the NGO, besides also considering the disturbed mental and psychological impact on the victim and so as not to be traumatized, the Regional Police of DIY do legal protection in the form of rehabilitation.